Applied digital signal processing : theory and practice - Manolakis, Dimitris G.; Ingle, Vinay K. (New York : Cambridge University Press, 2011)
"Master the basic concepts and methodologies of digital signal processing with this systematic introduction, without the need for an extensive mathematical background. The authors lead the reader through the fundamental mathematical principles underlying the operation of key signal processing techniques, providing simple arguments and cases rather than detailed general proofs. Coverage of practical implementation, discussion of the limitations of particular methods and plentiful MATLAB illustrations allow readers to better connect theory and practice. A focus on algorithms that are of theoretical importance or useful in real-world applications ensures that students cover material relevant to engineering practice, and equips students and practitioners alike with the basic principles necessary to apply DSP techniques to a variety of applications. Chapters include worked examples, problems and computer experiments, helping students to absorb the material they have just read. Lecture slides for all figures and solutions to the numerous problems are available to instructors"--
Machine generated contents note: 1. Introduction; 2. Discrete-time signals and systems; 3. The z-transform; 4. Fourier analysis of signals; 5. Transform analysis of LTI systems; 6. Sampling theory and practice; 7. The discrete Fourier transform; 8. Computation of the discrete Fourier transform; 9. Structures for discrete-time systems; 10. Filter design techniques; 11. Sampling rate conversion; 12. Filter banks; 13. Random signals; 14. Spectral analysis and optimum filtering; 15. Practical considerations.
Includes bibliographical references (p. [968]-976) and index.
Keywords: Signal processing